Association Between Internet Use, Cognitive Function, and Globus Pallidus Volumes: A Study Among the Elderly in Chinese Communities - Li, Wei; Yue, Ling; Xiao, Shifu (Frontiers in Public Health, 2022)
Abstract Background Previous studies have linked internet use with several beneficial outcomes for brain health, but there is little data on this among older Chinese. Objective The goal of this study was to explore the association between Internet use and cognitive impairment and to explore the possible mechanisms by which Internet use prevents cognitive decline. Methods The current study consisted of two cohorts: one from the China Longitudinal Aging Study (CLAS), which included 610 older adults with mild cognitive impairment (MCI), 192 with dementia, and 2218 healthy older adults; the second cohort included 39 healthy adults from the Shanghai brain health foundation (SHBHF2016001), who underwent T1 cranial magnetic resonance imaging at baseline, from which their volumes of the hippocampus, amygdala, and globus pallidus were calculated. Moreover, they were also followed up for one year. Through standardized questionnaires, detailed general demographic information and internet use information was obtained. The cognitive diagnosis of each participant was made by attending psychiatrists at baseline, and their overall cognitive function was assessed by the mini-mental state examination (MMSE) and Montreal Cognitive Assessment (MoCA). Results In cohort 1, after controlling age, gender, smoker, tea drinker, take exercise, diabetes, and hypertension, we found that internet use was a protective factor for MCI (p=0.015, OR=0.478, 95%CI:0.264 0.867), but not for dementia (p=0.205, OR=0.393, 95%CI:0.093 1.665). In cohort 2, we found that the globus pallidus volume of Internet users was significantly larger than that of non-users, and the MMSE change score was lower (p<0.05). The results of linear regression analysis showed that the change of MMSE value was negatively correlated with the volume of left globus pallidus (T=-3.315, p=0.003). Conclusions Internet use is a protective factor for mild cognitive impairment among the Chinese elderly, and it may prevent a decline in cognitive decline by affecting the volume of the globus pallidus. Keywords Internet use, cognition, elderly, MRI, globus pallidus